ANALISIS BAURAN PEMASARAN DAN FAKTOR SOSIAL TERHADAP KEPUTUSAN MAHASISWA MEMILIH FAKULTAS NON KEDOKTERAN UNIVERSITAS XYZ - Hukama, Adhan (JURNAL MANAJEMEN BISNIS, 2019)
This study aimed to determine the effect of the marketing mix and social factors on the decision of the students who chose the Faculty of Medicine, University Non-XYZ. This type of research is explanatory research with a quantitative approach. Proportional sampling using stratified random sampling of 250 respondents using multiple linear regression analysis techniques. The results showed that the variables of product, pricing and social factors positive and significant impact on the decision-making college students of the Faculty of Medicine, University Non-XYZ. Two other variables, location, and promotion of positive and not significant. While physical evidence and no significant negative effect on a student's decision lecture at the University of XYZ.